Judicial Remedies for Breach of Custody Agreements (Hadhanah) in Divorce Proceedings: Evidence from Makassar Religious Court - Mughni, Muh Shodiq; Qadri, Muhammad Al-Lail; Azamy, Muhammad Mumtaz (Universitas Islam Negeri Alauddin Makassar, 2025)
Divorce often raises legal issues related to custody (child custody), especially when there is a breach of contract or violation of obligations by one of the parties, thereby creating new conflicts between former spouses and impacting the fulfillment of children's rights. This study aims to analyze the role of judges in handling post-divorce custody breaches, both in terms of prevention and enforcement, with a focus on practices in the Makassar Religious Court. This study uses a qualitative method with an empirical juridical approach that combines primary and secondary data. Data was collected through court observations, in-depth interviews with judges and related parties, analysis of court decisions, and a study of Islamic family law literature and national regulations. The results of the study show that the dominant forms of default include neglecting responsibility for the child, abandoning financial support, and attempting to prevent the other party from meeting the child. In terms of prevention, judges consider the principle of the best interests of the child, the age of the child, moral suitability, and the economic capacity of the parents before determining custody rights. Meanwhile, in enforcing the law against breaches that occur, judges provide legal recourse for aggrieved parties to file a lawsuit to revoke custody rights or revise custody decisions, thereby ensuring that the interests of the child are protected. This study shows that judges in the Religious Court do not merely perform formal judicial functions, but also play a protective role towards children by balancing Islamic legal norms, national regulations, and values of public interest. Strengthening the role of judges in addressing hadhanah breaches is important to provide legal certainty while ensuring the protection of children's rights after divorce.